ANALYSIS OF NAIVE BAYES METHODS ON SCHOLARSHIP ADMISSIONS AT SMKS AL-WASLIYAH 2 MERBAU - Hanggi Kurniawan; Ibnu Rasyid Munthe; Budianto Bangun (Jurnal Mantik, 2022)
Scholarships currently play an important role in the world of education. Scholarships are financial aid given to students to complete their education. Scholarships are awarded by governments, foundations, institutions, or other institutions. Each scholarship has certain requirements. Scholarship programs are highly desired by every student, especially high-achieving but economically constrained students. The form of participation of the community, institutions, and students themselves in participating in building the nation, especially in the field of education, is crucial. By using the nave Bayes method, it is expected that the determination of scholarship recipients will be more targeted and accurate. This method serves to classify scholarship recipients into SMKs Alwasliyah 2 merbau. The Nave Bayes methods have no rules for their use. This method is used using benchmarks from the classification of pre-existing data